2006
DOI: 10.1677/joe.1.06857
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor kinase 2 and β-arrestins are recruited to FSH receptor in stimulated rat primary Sertoli cells

Abstract: FSH-receptor (FSH-R) signaling is regulated by agonistinduced desensitization and internalization. It has been shown, in a variety of overexpression systems, that G protein-coupled receptor kinases (GRKs) phosphorylate the activated FSH-R, promote b-arrestin recruitment and ultimately lead to internalization. The accuracy of this mechanism has not yet been demonstrated in cells expressing these different molecules at physiological levels. Using sucrose gradient fractionation, we show that FSH induces the recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…7C, D). In addition, as expected, b-arrestins were recruited to the FSHR in an FSH-dependent manner (23)(24)(25). However, we observed that p70S6K was not part of the complex (Fig.…”
Section: Fsh-stimulated P70s6k Activity Within the B-arrestin Scaffolsupporting
confidence: 79%
See 2 more Smart Citations
“…7C, D). In addition, as expected, b-arrestins were recruited to the FSHR in an FSH-dependent manner (23)(24)(25). However, we observed that p70S6K was not part of the complex (Fig.…”
Section: Fsh-stimulated P70s6k Activity Within the B-arrestin Scaffolsupporting
confidence: 79%
“…Our previous data indicated that the FSHR recruits b-arrestins upon ligand binding, promoting its desensitization, internalization (23,24), and ERK MAP kinase activation (25). Another FSHR-targeted signaling effector is p70S6K, as we and others had shown (6,7,47).…”
Section: Gene Ontology Analysis Of B-arrestin Interaction Partnersmentioning
confidence: 87%
See 1 more Smart Citation
“…For instance, G protein-coupled receptor kinases (GRKs) and dual-specific A kinase-anchoring protein 2, AKAP10 (also known as D-AKAP2), are expressed in the mouse testis [4][5][6]. Further studies demonstrated that ADRBK1 (also known as GRK2) is recruited to FSH receptors in stimulated primary rat Sertoli cells [5], and GRK4 is expressed in spermatozoa and germinal cells, where it is associated with mitochondrial and acrosomal membranes [4]. Here, we report a new RGS gene, regulator of G-protein signaling 22 (RGS22), that is specifically expressed in the human and mouse testis during different stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…β-arrestins are proteins endowed with regulatory scaffolding properties, which are generic to most GPCRs [46]. Recently, data have pointed to the instrumental role of β-arrestins as direct interactors with the FSH-R involved in the spatial and temporal organization of these signaling events [47][48][49]. These observations led to the concept that ligands with FSH activity could select only part of the signaling repertoire induced by the natural hormone, either G protein-dependent or β-arrestin-dependent [50,51].…”
Section: New Gonadotropin Receptor Signaling Pathwaysmentioning
confidence: 99%